Inside Outside Circle Model Assisted by Audio-Visual Media to Improve Science Cognitive Learning Outcomes of Fourth Grade Elementary School Students - Antari, Ni Kadek Novi; Agung, Anak Agung Gede; Ambra, Didith Pramunditya (Jurnal Pedagogi dan Pembelajaran, 2024)
The problem that occurs is that the science learning method in elementary schools tends to still use the lecture method, without student participation in the learning process. This research aims to evaluate the effect of implementing the IOC model assisted by audio-visual media on science cognitive learning outcomes in fourth grade elementary school students. This research uses a quasi-experimental design with a non-equivalent control group design. The population consisted of 386 fourth grade students in elementary school. Samples were taken using cluster random sampling technique, with 30 students as the experimental group and 31 students as the control group. Data collection methods and instruments were carried out using description tests. The collected data was analyzed using descriptive statistical techniques to describe sample characteristics, as well as pooled variances inferential statistical techniques (t-test) to compare learning outcomes between the experimental and control groups. The results of the analysis indicate rejection of the null hypothesis (H0) and acceptance of the alternative hypothesis (H1), which shows that there are significant differences between the two groups in terms of learning outcomes. Thus, it can be concluded that the application of the IOC model assisted by audio-visual media is effective in improving cognitive science learning outcomes in fourth grade elementary school students. It is hoped that the implications of this research will be an example for teachers in applying the IOC learning model to science learning.